A concrete based on waste wind power blades and a preparation method and application thereof

CN122977772APending Publication Date: 2026-10-27NINGXIA INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611476500.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]将废弃风电叶片纤维直接掺入混凝土,虽能在一定程度上提升抗折强度,但纤维表面残留的环氧树脂及脱模剂使其表面光滑、化学惰性强,与水泥水化产物的界面结合极弱,纤维受力后易从水泥基体中被拔出而非拉断,抑制裂缝扩展的作用无法充分发挥

Benefits of technology

(1)抗渗性能方面,本发明核层经环氧开环接枝活化后,端氨基超支化聚酰胺在废弃风电叶片纤维表面引入大量活性氨基,使废弃风电叶片纤维由疏水惰性表面转变为化学活性表面,这一转变为中间层的稳定沉积提供了化学锚点,同时活性氨基可参与水泥水化产物的成核与生长过程,在复合改性纤维-水泥基体界面形成化学键合,从根源上避免界面脱粘产生的微裂缝成为水的渗透通道。在核层提供的化学锚定基础上,中间层的氧化石墨烯通过其含氧官能团与核层表面的氨基形成稳固结合,氧化石墨烯能够调控水泥水化产物的微观形貌、减小界面过渡区的孔隙率并优化孔径分布,纳米碳酸钙则填充于复合改性纤维表面的微米级孔隙中,进一步压缩界面区域的毛细孔通道,当微裂纹在界面过渡区萌生时,氧化石墨烯与纳米碳酸钙在不同尺度上发挥填充与桥接作用,抑制微裂纹扩展,维持界面结构的完整性。中间层既填补了核层活化后暴露的微观缺陷,又为外层疏水单分子层的锚定提供了富含活性位点的基底。外层中,1H,1H,2H,2H-全氟癸基三乙氧基硅烷通过水解生成的硅羟基与中间层氧化石墨烯表面的含氧官能团形成化学键合,全氟碳链赋予复合改性纤维表面极低的表面能,使水分子难以在复合改性纤维表面铺展和渗透,提高了水分侵入界面区域的阈值压力,且该疏水层通过化学键固定在中间层表面。复合改性纤维三层结构中,核层解决了复合改性纤维表面活性位点缺失的问题,为界面结合提供化学基础;中间层在核层与水泥基体之间充当过渡纽带,既填充核层表面残留的微观孔隙、抑制界面裂纹萌生,又为外层的稳定结合提供化学桥梁;外层则在核层和中间层已消除的界面缺陷基础之上,构建一道额外的疏水屏障,使水分即使在穿透中间层的密实结构后仍无法进一步沿界面渗入。三层从界面化学活性、界面孔隙率和界面润湿性三个维度逐级发挥作用,每完成一层功能即为下一层创造更有利的作用条件,使水分沿复合改性纤维-水泥基体界面的渗透路径在多重阻隔下被有效延长,最终表现为混凝土抗渗等级的提升和渗水深度的降低。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of concrete, and relates to concrete based on waste wind power blades and a preparation method and application thereof.Aiming at the problem that the interface combination of waste wind power blade fibers mixed into concrete is weak and the anti-permeability performance is reduced, the application provides concrete based on waste wind power blades, which comprises 420-530 parts by mass of cement, 1.5-4 parts by mass of water reducing agent, 650-750 parts by mass of river sand, 1000-1150 parts by mass of gravel, 10-20 parts by mass of composite modified fibers and 170-200 parts by mass of water; the composite modified fibers have a core-intermediate layer-outer layer structure, the waste wind power blade fibers activated by epoxy ring opening grafting are used as the core, the graphene oxide / nano calcium carbonate composite layer deposited on the surface of the core is used as the intermediate layer, and the 1H, 1H, 2H, 2H-perfluorodecyl triethoxysilane self-assembled monolayer is used as the outer layer.The application can improve the anti-permeability performance without sacrificing the flexural strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of concrete technology, and relates to a concrete based on waste wind turbine blades, its preparation method and application. Background Technology

[0002] Wind turbine blades are primarily composed of glass fiber reinforced composite materials, which are difficult to degrade naturally and recycle efficiently after being discarded. The accumulation of large quantities of decommissioned blades occupies land resources, becoming an environmental problem that the wind power industry urgently needs to address. Crushing discarded wind turbine blades and incorporating them as fiber components into concrete is an important direction for realizing their resource utilization.

[0003] While directly incorporating waste wind turbine blade fibers into concrete can improve flexural strength to some extent, the residual epoxy resin and release agent on the fiber surface make it smooth and chemically inert, resulting in extremely weak interfacial bonding with cement hydration products. Under stress, the fibers are easily pulled out of the cement matrix rather than broken, thus failing to fully exert their effect of inhibiting crack propagation. Simultaneously, the fiber incorporation introduces numerous interfacial defects and additional pores into the concrete, making it easier for moisture and corrosive media to penetrate along the interface. The concrete's impermeability decreases with increasing fiber content. This means that existing methods sacrifice impermeability while improving flexural strength, making it difficult to meet the high durability requirements of concrete structures in humid environments such as marine environments and wastewater treatment facilities. If interfacial modification methods can be used to retain the flexural strengthening advantages of waste wind turbine blade fibers while eliminating their negative impact on impermeability, it is hoped that these technical bottlenecks can be overcome.

[0004] Therefore, developing a waste wind turbine blade-based concrete material that can effectively improve the impermeability of concrete structures without sacrificing flexural strength is of great practical significance. Summary of the Invention

[0005] This invention proposes a concrete based on waste wind turbine blades, its preparation method, and its application, aiming to solve the problems existing in the prior art.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows: On the one hand, the present invention provides a concrete based on waste wind turbine blades, wherein the concrete comprises, by weight, 420-530 parts cement, 1.5-4 parts water-reducing agent, 650-750 parts river sand, 1000-1150 parts crushed stone, 10-20 parts composite modified fiber and 170-200 parts water; The composite modified fiber has a core-intermediate layer-outer layer structure; The composite modified fiber uses waste wind turbine blade fiber activated by epoxy ring-opening grafting as the core, graphene oxide / nano-calcium carbonate composite layer deposited on the core surface as the middle layer, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane self-assembled monolayer anchored on the surface of the middle layer as the outer layer. The epoxy ring-opening graft activation method for the waste wind turbine blade fibers includes the following steps: dispersing the waste wind turbine blade fibers in N,N-dimethylformamide, adding terminal amino hyperbranched polyamide, and stirring and reacting at 60-80℃ for 4-12h under nitrogen protection; after the reaction is completed, washing successively with acetic acid aqueous solution with a volume percentage concentration of 50%-90%, deionized water, and anhydrous ethanol, and then vacuum drying.

[0007] Furthermore, in the composite modified fiber, the mass ratio of the core, intermediate layer and outer layer is 1:0.05-0.15:0.01-0.05.

[0008] Furthermore, in the epoxy ring-opening graft activation method for the waste wind turbine blade fibers, the mass-to-volume ratio of the waste wind turbine blade fibers to N,N-dimethylformamide is 1g:15-30mL.

[0009] Furthermore, in the epoxy ring-opening graft activation method for the waste wind turbine blade fibers, the mass ratio of terminal amino hyperbranched polyamide to waste wind turbine blade fibers is 1:10-20.

[0010] Furthermore, the method for preparing the waste wind turbine blade fiber includes the following steps: cutting, crushing, grinding, and sieving the waste wind turbine blade, collecting fiber components with a length of 5-50 mm, washing, and drying to obtain the fiber.

[0011] Furthermore, in the graphene oxide / nano-calcium carbonate composite layer, the mass ratio of graphene oxide to nano-calcium carbonate is 1:1-5.

[0012] Furthermore, the cement is P·O 42.5 ordinary Portland cement.

[0013] Furthermore, the water-reducing agent is a polycarboxylate water-reducing agent.

[0014] Furthermore, the preparation method of the composite modified fiber includes the following steps: Waste wind turbine blade fibers were dispersed in N,N-dimethylformamide, and amino-terminated hyperbranched polyamide was added. The mixture was stirred and reacted at 60-80℃ for 4-12 hours under nitrogen protection. After the reaction was completed, the fibers were washed successively with acetic acid aqueous solution (50%-90% by volume), deionized water, and anhydrous ethanol, and then vacuum dried to obtain epoxy ring-opening graft activated waste wind turbine blade fibers (activated fibers). Graphene oxide was ultrasonically dispersed in deionized water to obtain a graphene oxide dispersion; nano-calcium carbonate was ultrasonically dispersed in deionized water to obtain a nano-calcium carbonate suspension; the nano-calcium carbonate suspension was slowly added dropwise to the graphene oxide dispersion under mechanical stirring; after the addition was completed, ultrasonic treatment was continued to obtain a graphene oxide / nano-calcium carbonate composite dispersion; activated fibers were added to the graphene oxide / nano-calcium carbonate composite dispersion and stirred at room temperature for reaction; after the reaction was completed, the activated fibers were taken out, washed, and vacuum dried to obtain activated fibers in the middle layer of the graphene oxide / nano-calcium carbonate composite layer deposited on the surface. The activated fibers of the intermediate layer of the surface-deposited graphene oxide / nano-calcium carbonate composite layer were dispersed in anhydrous ethanol / water mixed solution containing 1H,1H,2H,2H-perfluorodecyltriethoxysilane; the self-assembly reaction was allowed to proceed at room temperature; after the reaction was completed, the fibers were washed and vacuum dried to obtain composite modified fibers with a core-intermediate-outer layer structure.

[0015] After the core layer is activated by epoxy ring-opening grafting, a large number of active amino groups are introduced into the surface of the waste wind turbine blade fibers. The terminal amino hyperbranched polyamide molecule is rich in primary and secondary amino groups, which endow the surface of the waste wind turbine blade fibers with chemical reactivity. The graphene oxide molecule contains a large number of carboxyl, hydroxyl and epoxy groups. When the activated fibers are mixed with the graphene oxide / nano-calcium carbonate composite dispersion, the carboxyl groups on the surface of graphene oxide undergo amidation reaction with the amino groups on the surface of the core layer to form amide bonds. At the same time, the epoxy groups on the surface of graphene oxide can be nucleophilically attacked by amino groups, undergoing ring-opening addition reaction to generate CN covalent bonds. The above chemical reactions enable graphene oxide to be firmly grafted onto the surface of the activated fibers in the form of covalent bonds. Nano-calcium carbonate is dispersed in the form of nanoparticles in a composite dispersion and loaded on the surface of graphene oxide sheets or embedded between graphene oxide sheets. It is deposited together with graphene oxide onto the surface of activated fibers to form a composite layer structure composed of graphene oxide and nano-calcium carbonate. In addition, the amino groups on the surface of activated fibers are protonated in water and become positively charged, while the carboxyl and hydroxyl groups on the surface of graphene oxide make them negatively charged in water. There is an electrostatic attraction between the two, which promotes the enrichment and deposition of graphene oxide onto the surface of activated fibers.

[0016] In anhydrous ethanol / water mixed solution, the three ethoxy groups of 1H,1H,2H,2H-perfluorodecyltriethoxysilane undergo hydrolysis in the presence of water to generate silanol groups. These silanol groups are highly reactive and can undergo condensation reactions with oxygen-containing functional groups on the surface of the intermediate layer of graphene oxide. Specifically, the silanol groups undergo dehydration condensation with the hydroxyl groups on the graphene oxide surface to form Si-OC covalent bonds. The silanol groups can also undergo condensation reactions with carboxyl groups on the graphene oxide surface, similarly forming Si-OC covalent bonds and losing one molecule of water. The key point is that, through the above condensation reaction, 1H,1H,2H,2H-perfluorodecyltriethoxysilane is chemically anchored to the surface of the intermediate layer in the form of covalent bonds. At the same time, the silanol groups generated by the hydrolysis between adjacent silane molecules can also condense with each other to form a Si-O-Si cross-linked network, so that the self-assembled monolayer forms a continuous and dense covering structure on the surface of the intermediate layer. After anchoring, the perfluorocarbon chains of the silane molecules are arranged outward, giving the surface of the composite modified fiber a low surface energy characteristic, making it difficult for water molecules to spread and penetrate on the surface of the composite modified fiber.

[0017] Both interfaces (core → intermediate layer, intermediate layer → outer layer) are dominated by covalent / chemical bonds, ensuring that the composite modified fiber maintains the integrity and stability of the interface structure in the temperature rise generated by the heat of hydration inside the concrete and in the high humidity environment. This effectively prolongs the water penetration path along the composite modified fiber-cement matrix interface, ultimately resulting in an improvement in the concrete's impermeability grade and a reduction in the water penetration depth.

[0018] On the other hand, a method for preparing concrete according to the present invention is provided, the method comprising the following steps: S1. Add the composite modified fiber to water accounting for 60%-80% of the total water mass, and stir at 200-400 r / min for 2-5 min to obtain a fiber dispersion; S2. Add cement, river sand, and crushed stone to the mixer and dry mix at a speed of 30-45 r / min for 30-60 seconds to ensure that the components are evenly mixed. Then add the fiber dispersion obtained in step S1 to the mixer, followed by the water-reducing agent and the remaining water. First, mix at a speed of 30-45 r / min for 60-90 seconds, then mix at a speed of 60-90 r / min for 90-150 seconds to obtain the concrete mixture. S3. Pour the concrete mixture obtained in step S2 into the mold, vibrate it to make it dense, and cure it for no less than 28 days under the conditions of temperature 20±2℃ and relative humidity ≥95%.

[0019] The present invention also provides the application of the concrete described herein in improving the impermeability of concrete structures.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) Regarding impermeability, after the core layer of this invention is activated by epoxy ring-opening grafting, the terminal amino hyperbranched polyamide introduces a large number of active amino groups on the surface of the waste wind turbine blade fibers, transforming the waste wind turbine blade fibers from a hydrophobic and inert surface to a chemically active surface. This transformation provides a chemical anchor for the stable deposition of the intermediate layer. At the same time, the active amino groups can participate in the nucleation and growth process of cement hydration products, forming chemical bonds at the interface of the composite modified fiber-cement matrix, thus preventing the microcracks caused by interface debonding from becoming water infiltration channels. Based on the chemical anchoring provided by the core layer, the graphene oxide in the intermediate layer forms a stable bond with the amino groups on the surface of the core layer through its oxygen-containing functional groups. Graphene oxide can regulate the microstructure of cement hydration products, reduce the porosity of the interface transition zone, and optimize the pore size distribution. Nano-calcium carbonate fills the micron-sized pores on the surface of the composite modified fiber, further compressing the capillary channels in the interface region. When microcracks initiate in the interface transition zone, graphene oxide and nano-calcium carbonate play a filling and bridging role at different scales, inhibiting the propagation of microcracks and maintaining the integrity of the interface structure. The intermediate layer not only fills the microscopic defects exposed after the core layer is activated, but also provides a substrate rich in active sites for anchoring the outer hydrophobic monolayer. In the outer layer, the silanol groups generated by the hydrolysis of 1H,1H,2H,2H-perfluorodecyltriethoxysilane form chemical bonds with the oxygen-containing functional groups on the surface of the intermediate layer graphene oxide. The perfluorocarbon chain endows the surface of the composite modified fiber with extremely low surface energy, making it difficult for water molecules to spread and penetrate on the surface of the composite modified fiber, increasing the threshold pressure of water intrusion into the interface region, and this hydrophobic layer is fixed to the surface of the intermediate layer by chemical bonds. In the three-layer structure of the composite modified fiber, the core layer solves the problem of missing active sites on the surface of the composite modified fiber, providing a chemical basis for interfacial bonding. The middle layer acts as a transitional link between the core layer and the cement matrix, filling the micropores remaining on the surface of the core layer, inhibiting the initiation of interfacial cracks, and providing a chemical bridge for the stable bonding of the outer layer. The outer layer, based on the eliminated interfacial defects in the core and middle layers, constructs an additional hydrophobic barrier, preventing water from further penetrating along the interface even after penetrating the dense structure of the middle layer. The three layers function sequentially from three dimensions: interfacial chemical activity, interfacial porosity, and interfacial wettability. Each completed function of one layer creates more favorable conditions for the next, effectively extending the water penetration path along the composite modified fiber-cement matrix interface under multiple barriers, ultimately resulting in an improvement in the concrete's impermeability and a reduction in the depth of water penetration.

[0021] (2) Regarding flexural strength, the insufficient interfacial bonding strength between the waste wind turbine blade fibers and the cement matrix in the existing technology is the core problem restricting the reinforcement effect. The waste wind turbine blade fibers have a smooth surface and strong chemical inertness, lacking effective chemical bonding and physical anchoring with cement hydration products. When subjected to force, the waste wind turbine blade fibers are easily pulled out of the cement matrix rather than broken, and the bridging and crack-preventing effects cannot be fully utilized. In this invention, the active amino groups introduced through activation of the core layer of the composite modified fiber change the surface of the composite modified fiber from inert to chemically active. The amino groups can participate in the nucleation and growth process of cement hydration products, forming chemical bonds at the interface of the composite modified fiber-cement matrix, changing the original weak interfacial bonding mode dominated by physical adsorption; the intermediate layer further improves the mechanical integrity of the interface area through dense filling and microcrack bridging; the outer layer indirectly ensures the sufficiency and uniformity of cement hydration in the interface area by blocking moisture intrusion. The three layers work together to provide the composite modified fiber with an anchoring force that resists interfacial debonding between the fiber and the cement matrix. The composite modified fiber can effectively transfer stress and inhibit crack propagation when the concrete is subjected to bending, thereby improving the impermeability without sacrificing flexural strength.

[0022] (3) The concrete preparation method of the present invention adopts a pre-dispersion-segmented mixing process of composite modified fiber, which avoids the agglomeration of composite modified fiber, ensures the uniform dispersion of composite modified fiber in concrete matrix, and ensures the stable realization of impermeability and flexural strength. Detailed Implementation

[0023] The technical solution of the present invention will be described below with reference to embodiments. However, the present invention is not limited to the following embodiments. Unless otherwise specified, the experimental methods and detection methods described in each embodiment are conventional methods; unless otherwise specified, the reagents and materials are all commercially available.

[0024] In this embodiment of the invention, the cement matrix refers to the continuous phase (i.e., cement stone) formed by cement hydration products, which is the finest continuous medium in concrete; it is used to describe the interfacial chemical bonding and interfacial transition zone structure between the composite modified fiber and the cement hydration products.

[0025] In this embodiment of the invention, the concrete matrix refers to the overall continuous phase medium after the concrete has hardened, including cement paste, capillaries, and unhydrated particles, etc., and is a continuous medium at the microscopic level; it is used to describe the dispersion state of the composite modified fiber in the concrete matrix and the interfacial bonding between the composite modified fiber and the concrete matrix.

[0026] In this embodiment of the invention, the river sand is natural river sand with a fineness modulus of 2.6.

[0027] In this embodiment of the invention, the crushed stone is natural crushed stone with a continuous gradation of 5-25mm.

[0028] In this embodiment of the invention, the method for preparing waste wind turbine blade fibers includes the following steps: waste wind turbine blades (the waste wind turbine blades are from a decommissioned wind farm in Ningxia, Northwest China) are cut into blocks by a cutting machine, and then fed into a crusher for crushing. The crushed material is ground by a grinder and screened by a vibrating screen to collect fiber components with a length of 5-50 mm. The screened fiber components are washed with deionized water 2-4 times to remove dust and impurities attached to the surface, and dried at 60-80℃ for 12-24 hours to obtain the fiber.

[0029] In this embodiment of the invention, the method for preparing composite modified fibers includes the following steps: Waste wind turbine blade fibers were dispersed in N,N-dimethylformamide, and amino-terminated hyperbranched polyamide was added. The mixture was stirred and reacted at 60-80℃ for 4-12 hours under nitrogen protection. After the reaction, the fibers were washed 2-4 times with 50%-90% (v / v) acetic acid aqueous solution, deionized water, and anhydrous ethanol, respectively, and then vacuum dried at 55-65℃ for 12-20 hours to obtain activated fibers. Graphene oxide was ultrasonically dispersed in 90-120 mL of deionized water (power 180-240 W, frequency 38-42 kHz, ultrasonic treatment for 1-2 h) to obtain a graphene oxide dispersion. Nano-calcium carbonate was ultrasonically dispersed in 45-60 mL of deionized water (power 180-240 W, frequency 38-42 kHz, ultrasonic treatment for 25-35 min) to obtain a nano-calcium carbonate suspension. The nano-calcium carbonate suspension was slowly added dropwise to the graphene oxide dispersion under mechanical stirring (250-350 r / min), with the addition time controlled at 25-40 min. After the addition was complete, the process continued... The mixture was ultrasonically treated for 40-60 min (power 180-240 W, frequency 38-42 kHz) to obtain a graphene oxide / nano-calcium carbonate composite dispersion. Activated fibers were added to the graphene oxide / nano-calcium carbonate composite dispersion and stirred at 250-350 r / min for 8-15 min. Subsequently, the reaction was continued at 250-350 r / min at room temperature for 2.5-4 h. After the reaction was completed, the activated fibers were removed, washed 2-4 times with deionized water, and vacuum dried at 55-65℃ for 12-20 h to obtain activated fibers with a surface-deposited graphene oxide / nano-calcium carbonate composite intermediate layer. Activated fibers with a surface-deposited graphene oxide / nano-calcium carbonate composite intermediate layer were dispersed in anhydrous ethanol / water mixed solution containing 1H,1H,2H,2H-perfluorodecyltriethoxysilane (mass percentage concentration of 0.5%-1.2%) and allowed to self-assemble at room temperature for 4-10 h. After the reaction, the fibers were washed 2-4 times with anhydrous ethanol and deionized water, and then vacuum dried at 55-65℃ for 12-20 h to obtain composite modified fibers with a core-intermediate-outer layer structure.

[0030] Example 1 This embodiment provides a concrete based on waste wind turbine blades. By weight, the concrete comprises 420 parts cement (P·O 42.5 ordinary Portland cement), 1.5 parts water-reducing agent (polycarboxylate water-reducing agent), 650 parts river sand, 1000 parts crushed stone, 10 parts composite modified fiber and 170 parts water. The composite modified fiber has a core-intermediate layer-outer layer structure; the composite modified fiber uses waste wind turbine blade fiber activated by epoxy ring-opening grafting as the core, graphene oxide / nano-calcium carbonate composite layer deposited on the core surface as the intermediate layer, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane self-assembled monolayer anchored on the surface of the intermediate layer as the outer layer. The epoxy ring-opening graft activation method for the waste wind turbine blade fibers includes the following steps: dispersing the waste wind turbine blade fibers in N,N-dimethylformamide, adding terminal amino hyperbranched polyamide, and stirring and reacting at 60°C for 4 hours under nitrogen protection; after the reaction, washing twice each with a 50% (v / v) aqueous acetic acid solution, deionized water, and anhydrous ethanol, and then vacuum drying (55°C, 12 hours). In the composite modified fiber, the mass ratio of the core, intermediate layer, and outer layer is 1:0.05:0.01; In the epoxy ring-opening graft activation method for the waste wind turbine blade fibers, the mass-volume ratio of waste wind turbine blade fibers to N,N-dimethylformamide is 1g:15mL, and the mass ratio of terminal amino hyperbranched polyamide to waste wind turbine blade fibers is 1:10. In the graphene oxide / nano-calcium carbonate composite layer, the mass ratio of graphene oxide to nano-calcium carbonate is 1:1.

[0031] Example 2 This embodiment provides a concrete based on waste wind turbine blades. By weight, the concrete comprises 530 parts cement (P·O 42.5 ordinary Portland cement), 4 parts water-reducing agent (polycarboxylate water-reducing agent), 750 parts river sand, 1150 parts crushed stone, 20 parts composite modified fiber and 200 parts water. The composite modified fiber has a core-intermediate layer-outer layer structure; the composite modified fiber uses waste wind turbine blade fiber activated by epoxy ring-opening grafting as the core, graphene oxide / nano-calcium carbonate composite layer deposited on the core surface as the intermediate layer, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane self-assembled monolayer anchored on the surface of the intermediate layer as the outer layer. The epoxy ring-opening graft activation method for the waste wind turbine blade fibers includes the following steps: dispersing the waste wind turbine blade fibers in N,N-dimethylformamide, adding amino-terminated hyperbranched polyamide, and stirring and reacting at 80°C for 12 hours under nitrogen protection; after the reaction, washing the fibers four times each with a volume percentage concentration of 90% acetic acid aqueous solution, deionized water, and anhydrous ethanol, and then vacuum drying (65°C, 20 hours). In the composite modified fiber, the mass ratio of the core, intermediate layer, and outer layer is 1:0.15:0.05; In the epoxy ring-opening graft activation method for the waste wind turbine blade fibers, the mass-volume ratio of waste wind turbine blade fibers to N,N-dimethylformamide is 1g:30mL, and the mass ratio of terminal amino hyperbranched polyamide to waste wind turbine blade fibers is 1:20. In the graphene oxide / nano-calcium carbonate composite layer, the mass ratio of graphene oxide to nano-calcium carbonate is 1:5.

[0032] Example 3 This embodiment provides a concrete based on waste wind turbine blades. By weight, the concrete comprises 450 parts cement (P·O 42.5 ordinary Portland cement), 2 parts water-reducing agent (polycarboxylate water-reducing agent), 700 parts river sand, 1100 parts crushed stone, 12 parts composite modified fiber and 180 parts water. The composite modified fiber has a core-intermediate layer-outer layer structure; the composite modified fiber uses waste wind turbine blade fiber activated by epoxy ring-opening grafting as the core, graphene oxide / nano-calcium carbonate composite layer deposited on the core surface as the intermediate layer, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane self-assembled monolayer anchored on the surface of the intermediate layer as the outer layer. The epoxy ring-opening graft activation method for the waste wind turbine blade fibers includes the following steps: dispersing the waste wind turbine blade fibers in N,N-dimethylformamide, adding terminal amino hyperbranched polyamide, and stirring and reacting at 60°C for 8 hours under nitrogen protection; after the reaction, washing the fibers three times each with a volume percentage concentration of 50% acetic acid aqueous solution, deionized water, and anhydrous ethanol, and then vacuum drying (55°C, 15 hours). In the composite modified fiber, the mass ratio of the core, intermediate layer, and outer layer is 1:0.1:0.02; In the epoxy ring-opening graft activation method for waste wind turbine blade fibers, the mass-volume ratio of waste wind turbine blade fibers to N,N-dimethylformamide is 1g:20mL, and the mass ratio of terminal amino hyperbranched polyamide to waste wind turbine blade fibers is 1:15. In the graphene oxide / nano-calcium carbonate composite layer, the mass ratio of graphene oxide to nano-calcium carbonate is 1:2.

[0033] Example 4 This embodiment provides a method for preparing concrete, the method comprising the following steps: S1. Add the composite modified fiber to water accounting for 60%-80% of the total water mass, and stir at 200-400 r / min for 2-5 min to obtain a fiber dispersion; S2. Add cement, river sand, and crushed stone to a mixer (forced mixer) and dry mix at a speed of 30-45 r / min for 30-60 seconds to ensure uniform mixing of all components. Then add the fiber dispersion obtained in step S1 to the mixer, followed by the water-reducing agent and remaining water. First, mix at a speed of 30-45 r / min for 60-90 seconds, then mix at a speed of 60-90 r / min for 90-150 seconds to obtain the concrete mixture. S3. Pour the concrete mixture obtained in step S2 into the mold, vibrate it to make it dense, and cure it for no less than 28 days under the conditions of temperature 20±2℃ and relative humidity ≥95%.

[0034] Comparative Example 1 (nuclear inactivation) This comparative example is the same as Example 3, except that the core layer of the composite modified fiber is waste wind turbine blade fiber that has not been activated by epoxy ring-opening grafting, while the rest is the same as Example 3.

[0035] Comparative Example 2 (Physical Blending) This comparative example is the same as Example 3, except that: waste wind turbine blade fibers activated by epoxy ring-opening grafting, graphene oxide, nano-calcium carbonate, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane are directly physically blended and added, without preparing composite modified fibers with a core-intermediate-outer layer three-layer structure. Everything else remains the same as in Example 3.

[0036] Comparative Example 3 (without outer layer) This comparative example is the same as Example 3, except that the composite modified fiber is only prepared up to the core-intermediate layer structure and does not anchor the outer layer of the 1H,1H,2H,2H-perfluorodecyltriethoxysilane self-assembled monolayer. The rest is the same as in Example 3.

[0037] Comparative Example 4 (non-1H,1H,2H,2H-perfluorodecyltriethoxysilane) This comparative example is the same as Example 3, except that the outer layer of the composite modified fiber is a self-assembled monolayer of dodecyltrimethoxysilane instead of 1H,1H,2H,2H-perfluorodecyltriethoxysilane. The rest is the same as in Example 3.

[0038] Comparative Example 5 (blank, fiber-free) This comparative example is the same as Example 3, except that no composite modified fiber is added, that is, the concrete mix does not contain any fiber components, and the rest is the same as Example 3.

[0039] Comparative Example 6 (Untreated Fibers) This comparative example is the same as Example 3, except that the composite modified fiber is replaced with waste wind turbine blade fiber that has not been activated by epoxy ring-opening grafting, has not been deposited with graphene oxide / nano-calcium carbonate composite layer, and has not been anchored by 1H,1H,2H,2H-perfluorodecyltriethoxysilane self-assembled monolayer. The rest is the same as Example 3.

[0040] Effect verification I. Experimental Subjects: The concrete prepared according to the preparation method of Example 4 in Examples 1-3 and Comparative Examples 1-6 was cut into standard specimens. All specimens were cured in a standard curing room with a temperature of 20±2℃ and a relative humidity of ≥95% for 28 days.

[0041] II. Experimental Methods: 1. Test method for impermeability The test was conducted according to GB / T 50082-2024. Six specimens were used in each group for the impermeability test. The water pressure started at 0.1 MPa and increased by 0.1 MPa every 8 hours, while continuously observing the seepage on the top surface of the specimens. The test was stopped when seepage was observed on the top surface of three out of the six specimens, and the water pressure H (MPa) at this point was recorded. The impermeability grade was calculated using the formula P=10H-1. If, after pressurizing to 1.2 MPa, fewer than three specimens showed signs of seepage after 8 hours, the impermeability grade was recorded as P12. The impermeability grade achieved by each group of specimens was taken as the test result of the impermeability performance of that group of concrete.

[0042] The test was conducted in accordance with GB / T 50082-2024. Six specimens were taken from each group, and the water pressure was kept constant at 1.2 MPa for 24 hours. After depressurization, the specimens were split in the middle, and the seepage height was measured every 10 mm on the split surface. The arithmetic mean of all measuring points for each specimen was first calculated as the seepage height of that specimen. Then, the arithmetic mean of the seepage heights of the six specimens was taken as the seepage height of the concrete in that group (accurate to 1 mm).

[0043] 2. Flexural strength test method The test was conducted in accordance with GB / T 50081-2019. Three specimens were used in each group for flexural strength testing. The test results were determined according to the following rules: (1) The arithmetic mean of the three specimen measurements was taken as the flexural strength value of the group of specimens (accurate to 0.1 MPa); (2) When the difference between the maximum or minimum value and the median value among the three measurements exceeded 15% of the median value, the maximum and minimum values ​​were discarded, and the median value was taken as the flexural strength value of the group of specimens; (3) When the difference between the maximum and minimum values ​​and the median value both exceeded 15% of the median value, the test results of the group of specimens were invalid; 4) When the lower edge fracture location of one specimen is outside the lines of action of two concentrated loads, the measured value of that specimen should be discarded, and the flexural strength of the concrete should be calculated based on the test results of the other two specimens. If the difference between the two measured values ​​is not greater than 15% of the smaller of the two measured values, then the arithmetic mean of the two measured values ​​should be taken as the flexural strength value of the group of specimens; otherwise, the test results of the group of specimens are invalid. When the lower edge fracture locations of two specimens are outside the lines of action of two concentrated loads, the test results of the group of specimens are invalid.

[0044] III. Experimental Results: As shown in Table 1.

[0045] Table 1

[0046] Regarding the impermeability grade, as shown in Table 1, after the waste wind turbine blade fiber was directly incorporated into the concrete (Comparative Example 6), the impermeability grade decreased from P6 of the blank concrete (Comparative Example 5) to P4. It can be seen that the incorporation of fiber introduced a large number of interface defects and additional pores into the concrete, causing the impermeability of the concrete to decrease with the increase of fiber content. Comparative Example 1 (unactivated core) had a permeability grade of only P6, the same as blank concrete, indicating that the three-layer structure cannot be effectively formed when the core layer is not activated, and thus cannot effectively improve the permeability performance. Comparative Example 2 (physical blend) had a permeability grade of only P4, comparable to untreated fiber concrete, indicating that physical blending cannot achieve effective bonding between the components. Comparative Example 3 (no outer layer) had a permeability grade of P6, indicating that although the filling and compaction effect of the intermediate layer can restore the permeability to the blank level, the lack of an outer hydrophobic barrier still cannot achieve further improvement in the permeability grade. Comparative Example 4 (outer layer is dodecyltrimethoxysilane) had a permeability grade of P6, indicating that ordinary alkylsilanes, due to the lack of the low surface energy characteristics of perfluorocarbon chains, cannot construct an effective superhydrophobic barrier, and their hydrophobic effect is far inferior to 1H,1H,2H,2H-perfluorodecyltriethoxysilane. In contrast, the permeability grades of Examples 1-3 of this invention reached P8-P10, all significantly better than all comparative examples. The above results indicate that the core layer, after being activated by epoxy ring-opening grafting to introduce active amino groups, provides a chemical anchor for the stable deposition of the intermediate layer. The intermediate layer, composed of graphene oxide / nano-calcium carbonate, is chemically anchored to the core layer surface via covalent bonds, filling the micropores on the core layer surface and reducing the porosity of the interfacial transition zone. The outer layer, a self-assembled monolayer of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, is firmly bonded to the intermediate layer surface via Si-OC covalent bonds. The perfluorocarbon chains impart extremely low surface energy to the fiber surface, making it difficult for water molecules to spread and permeate. This three-layer structure works progressively, achieving a significant improvement in impermeability.

[0047] Regarding the seepage height, Table 1 shows that the seepage height of the blank concrete (Comparative Example 5) was 120 mm, while that of the untreated fiber-reinforced concrete (Comparative Example 6) increased to 150 mm, further verifying the negative impact of fiber incorporation on impermeability. The seepage heights of Comparative Examples 1-4 ranged from 105 to 145 mm, failing to effectively reduce the seepage height. In contrast, the seepage heights of Examples 1-3 of this invention were only 60-75 mm, significantly lower than all comparative examples, indicating that the step-by-step blocking effect of the three-layer structure on the water penetration path is the essential reason for the significant reduction in seepage height.

[0048] Regarding flexural strength, Table 1 shows that after the waste wind turbine blade fibers were directly incorporated into concrete (Comparative Example 6), the flexural strength increased from 5.1 MPa in blank concrete (Comparative Example 5) to 5.5 MPa, indicating that fibers can improve flexural strength to a certain extent. The flexural strength of Comparative Example 1 (unactivated core) was only 5.2 MPa, basically the same as the blank concrete, indicating that the fibers could not play an effective reinforcing role when the core layer was not activated. The flexural strengths of Comparative Example 3 (no outer layer) and Comparative Example 4 (ordinary silane outer layer) were both 5.4 MPa, lower than Comparative Example 6 and Examples 1-3. In contrast, the flexural strengths of Examples 1-3 of this invention were 5.5-5.6 MPa, all higher than the blank concrete (5.1 MPa), and the same as or slightly higher than the untreated fiber-reinforced concrete (5.5 MPa). The above results indicate that the active amino groups introduced into the core layer of this invention through activation can form chemical bonds at the fiber-cement matrix interface, changing the original weak interfacial bonding mode dominated by physical adsorption; the intermediate layer further enhances the mechanical integrity of the interfacial region through dense filling and microcrack bridging; the outer layer indirectly ensures the sufficiency and uniformity of cement hydration in the interfacial region by blocking moisture intrusion, enabling the composite modified fiber and the cement matrix to have an anchoring force that resists interfacial debonding, and the fiber can effectively transfer stress and inhibit crack propagation when the concrete is subjected to bending, thereby improving the impermeability without sacrificing flexural strength.

[0049] It should be understood that the disclosed invention is not limited to the specific methods, schemes, and substances described, as these are all subject to variation. It should also be understood that the terminology used herein is for the purpose of describing specific embodiments only and is not intended to limit the scope of the invention, which is limited only by the appended claims.

Claims

1. A type of concrete based on discarded wind turbine blades, characterized in that, The concrete, by weight, comprises 420-530 parts cement, 1.5-4 parts water-reducing agent, 650-750 parts river sand, 1000-1150 parts crushed stone, 10-20 parts composite modified fiber and 170-200 parts water. The composite modified fiber has a core-intermediate layer-outer layer structure; The composite modified fiber uses waste wind turbine blade fiber activated by epoxy ring-opening grafting as the core, graphene oxide / nano-calcium carbonate composite layer deposited on the core surface as the middle layer, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane self-assembled monolayer anchored on the surface of the middle layer as the outer layer. The epoxy ring-opening graft activation method for the waste wind turbine blade fibers includes the following steps: dispersing the waste wind turbine blade fibers in N,N-dimethylformamide, adding terminal amino hyperbranched polyamide, and stirring and reacting at 60-80℃ for 4-12h under nitrogen protection; after the reaction is completed, washing successively with acetic acid aqueous solution with a volume percentage concentration of 50%-90%, deionized water, and anhydrous ethanol, and then vacuum drying.

2. The concrete according to claim 1, characterized in that, In the composite modified fiber, the mass ratio of the core, intermediate layer and outer layer is 1:0.05-0.15:0.01-0.

05.

3. The concrete according to claim 1, characterized in that, In the epoxy ring-opening graft activation method for waste wind turbine blade fibers, the mass-to-volume ratio of waste wind turbine blade fibers to N,N-dimethylformamide is 1g:15-30mL.

4. The concrete according to claim 1, characterized in that, In the epoxy ring-opening graft activation method for waste wind turbine blade fibers, the mass ratio of terminal amino hyperbranched polyamide to waste wind turbine blade fibers is 1:10-20.

5. The concrete according to claim 1, characterized in that, The method for preparing the waste wind turbine blade fiber includes the following steps: cutting, crushing, grinding, and sieving the waste wind turbine blade, collecting fiber components with a length of 5-50mm, washing and drying them to obtain the fiber.

6. The concrete according to claim 1, characterized in that, In the graphene oxide / nano-calcium carbonate composite layer, the mass ratio of graphene oxide to nano-calcium carbonate is 1:1-5.

7. The concrete according to claim 1, characterized in that, The cement is P·O 42.5 ordinary Portland cement.

8. The concrete according to claim 1, characterized in that, The water-reducing agent is a polycarboxylate water-reducing agent.

9. The method for preparing concrete according to any one of claims 1-8, characterized in that, The preparation method includes the following steps: S1. Add the composite modified fiber to water accounting for 60%-80% of the total water mass, and stir at 200-400 r / min for 2-5 min to obtain a fiber dispersion; S2. Add cement, river sand, and crushed stone to the mixer and dry mix at a speed of 30-45 r / min for 30-60 seconds to ensure that the components are evenly mixed. Then add the fiber dispersion obtained in step S1 to the mixer, followed by the water-reducing agent and the remaining water. First, mix at a speed of 30-45 r / min for 60-90 seconds, then mix at a speed of 60-90 r / min for 90-150 seconds to obtain the concrete mixture. S3. Pour the concrete mixture obtained in step S2 into the mold, vibrate it to make it dense, and cure it for no less than 28 days under the conditions of temperature 20±2℃ and relative humidity ≥95%.

10. The application of the concrete according to any one of claims 1-8 in improving the impermeability of concrete structures.